Suplemen Calcitriol Dosis Tinggi Mencegah Osteoporosis dan Memicu Urolitiasis pada Tikus Ovariektomi - hartiningsih hartiningsih; devita anggraeni (Jurnal Sain Veteriner, 2021)
Calcitriol supplementation in ovariectomized rats for 8 weeks reduce osteoporosis risk and safe for kidney depend a proper dose. The objective of the research was to study the efectivity of high dose calcitriol for osteoporosis prevention and safe for kidney  in ovariectomized Wistar rats. Fifteen female Wistar rats at 8 weeks of age were randomly divided into three  groups of five which were sham operated rats (KN), ovariectomized rats (KOV), and ovariectomized rats+calcitriol supplementation 200ng/day (OVD200). After 8 weeks of treatment, blood samples were taken from plexus orbitalis medialis for estrogen analysis. All rats were then euthanized, left tibia and left kidney were taken for histopathological examination using hematoxylin and eosin stain. Immunohistochemistry using anti TRAP5b monoclonal antibody was also done for left tibia by streptavidin-biotin.  The results showed that estradiol level of KOV was significantly decreased compared with KN (P<0.05), meanwhile, estradiol levels of OVD200 were not significantly different compared with KOV. Histopathologic figure of kidney in KOV was not different compared with KN. Glomerulus was surrounded by Bowman‘s capsule, proximal and distal convoluted tubulus were lined with typical cuboidal epithelium. Immunohistochemistry result of proximal tibial epiphysis in KOV were shown more tartrate resistant alkaline phosphatase 5b (TRAP5b) expression in trabecular bone, which was located in bone marrow space, and trabecular speculum surface as well. Meanwhile, proximal tibia epiphysis in OVD200 had less tartrate resistant alkaline phosphatase 5b (TRAP5b) expression compared with KOV. Histopathologic figure  of proximal tibia epiphysis in group OVD200 was shown more trabecular bone speculum and less adipocyte in the bone marrow compared with KOV. Histopathologic figure of kidney in OVD200 was showed glomerular  hypertrophy and atrophy, as well as protein deposits in proximal convoluted tubules epithelium.  In conclusion, calcitriol supplementation 200ng/day in ovariectomized rats for 8 weeks prevented osteoporosis risk but trigger urolithiasis. Key words :  : Calcitriol, osteoporosis, ovariectomized rats, urolithiasis